Reverse smoking and its effects among indian reverse smokers: A scoping review - Divya Vinnakota; Saira Hakkim; Maneesha Varghese Pellissery; Madhini Sivasubramanian; Mohammad Tariqul Islam Khan; Afroza Hoque; Abu Rushd Mohammad Mashrur; Ali Davod Parsa; Russell Kabir (Wolters Kluwer Medknow Publications, 2022)
Reverse smoking is a unique style of tobacco use in which the smoker places the lit end of a chutta into his or her mouth while smoking and then inhales the smoke from the lit end. The purpose of this scoping review is to explore reverse smoking and identify its effects among Indian reverse smokers. Literature search was conducted using PubMed, PubMed Central, Embase, and CINAHL Plus. Boolean operators AND/OR was used with the search terms. Search was limited to the original research articles, English language articles, and full-text articles. Finally seven original articles were selected for the scoping review. The studies were conducted between 1971 and 2016, where more studies were identified in the 21st century (2002-2016). Four themes emerged from the data analysis. The first themes explore the palatal mucosal changes in reverse smokers; the second theme presents carcinoma and reverse smoking; third theme focuses on effects of keratinization on detection of epithelial atypia, and lastly, the fourth theme focuses on reverse smoking and psychosocial factors. Reverse smokers are more likely to develop precancerous palatal alterations and squamous cell carcinoma of the palate. To make healthy choices, a strong focus on health promotion is required, which includes initiatives that emphasize the need of educating individuals about disease risks.